Etnomatematika Melalui Inovasi Pembelajaran Matematika di Sekolah Dasar GMIT 034 Wolwal - Desi Natalia Auw; Mariana Mungkabel; Melki Imamastri Puling Tang (Yayasan Literasi Sains Indonesia, 2023)
Innovation in learning mathematics needs to be done so that the goals of learning mathematics can be achieved effectively. One of the innovations that can be done is to utilize Alor cultural products (Wolwal Village) in learning mathematics. Besides being able to learn mathematics well, students can also get to know their culture which is slowly being forgotten. This study aims to describe the results of an ethnomathematics exploration of the culture of Alor (Wolwal Village) which can be utilized in learning mathematics. Community service activities are carried out with assistance in learning ethnomathematics-based mathematics through participatory action research (PAR) service, namely action service as a result of the service process with the stages of preparation, implementation, evaluation and reflection 1) in the preparation stage, the community service team conducts surveys and discussions with partners namely the principal and homeroom teacher as well as the mathematics subject teacher at SD GMIT 034 Wolwal; 2) The stage of implementing activities for grade 1 students at SD GMIT 034 Wolwal by delivering material and ethnomathematics practices, namely the traditional siki doka game related to mathematics. In connection with this activity, the author tries to gather information through literature, observations and interviews with one of the teachers of SD GMIT 034 Wolwal who is a Wolwal native who knows information about the object to be explored. The results of the study show that there are many cultural products in Wolwal Village that have the potential for learning mathematics, for example cultural products in the form of traditional food, traditional games, handicrafts, and so on. If the cultural products of Wolwal Village can be used properly in learning mathematics, then it will create meaningful learning for SD GMIT 034 Wolwal students.